2017
DOI: 10.1039/c6sc04169h
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular assembly of platinum-containing polyhedral oligomeric silsesquioxanes: an interplay of intermolecular interactions and a correlation between structural modifications and morphological transformations

Abstract: POSS-functionalized platinum(ii) complexes demonstrate systematically controllable morphological transformations through interplay of intermolecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 82 publications
0
37
0
Order By: Relevance
“…49,50 As a result of these non-covalent interactions, planar Pt(II) complexes have been reported to aggregate into a range of morphologies on the micron length scale, including fibers, ribbons and vesicles. [51][52][53][54][55][56][57] The resulting materials are of interest due to their electronic and emissive properties, 38 resistance to photobleaching, 58 low energy red or near IR excitation for bioimaging applications, 39 and potential anticancer activity. 42 Although alterations to the solvating ligands and solvent conditions can modify the aggregation behavior, most commonly thick, multi-micron long fibers are formed which rapidly result in gelation as a result of low colloidal stability.…”
Section: Abstract: Self-assembly • Kinetic Control • Metallophilic Bomentioning
confidence: 99%
“…49,50 As a result of these non-covalent interactions, planar Pt(II) complexes have been reported to aggregate into a range of morphologies on the micron length scale, including fibers, ribbons and vesicles. [51][52][53][54][55][56][57] The resulting materials are of interest due to their electronic and emissive properties, 38 resistance to photobleaching, 58 low energy red or near IR excitation for bioimaging applications, 39 and potential anticancer activity. 42 Although alterations to the solvating ligands and solvent conditions can modify the aggregation behavior, most commonly thick, multi-micron long fibers are formed which rapidly result in gelation as a result of low colloidal stability.…”
Section: Abstract: Self-assembly • Kinetic Control • Metallophilic Bomentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Furthermore, when Pt II complexes are close enough (distance below 3.5 ) [11][12][13][14] metallophilic interactions between Pt centers may be established and stable aggregates [15][16][17] can be observed that possess spectroscopic properties which can be dramatically different from those of the monomeric metal complex. [1][2][3][4][18][19][20][21][22][23] In fact, the establishmento fg round state intermolecular interactions between protruding d z 2 orbitals resultsi nt he formation of lower-lying molecular orbitals, thus an ew optical transition appears ascribed to metal-metal-to-ligand charget ransfer (MMLCT). [22][23][24][25][26][27][28] The changes in the optical properties are directly correlated with the distance between the Pt centers.…”
Section: Introductionmentioning
confidence: 99%
“…Such interactions have been identified on numerous occasions in Pt II terpyridyl complexes, both in the solids tate and in solution. [28][29][30][31][32][33][34][35][36][37] Square-planar d 8 metals bear filled d z 2 orbitals, which can overlap into ds and ds* bondinga nd antibonding molecular orbitals with the d z 2 orbital of as tacked neighbor. [38][39][40] The strength of the isolated PtÀ Pt interaction is significant, and reaches 4.2 kcal mol À1 in the case of the [Pt(tpy)Cl] 2 2 + dimer (unsubstituted tpy).…”
Section: Resultsmentioning
confidence: 99%
“…As studied in detail by Castellano, [48][49][50][51][52] Yam [29][30][31][32][33][34][35][36][37][53][54][55][56][57][58] and Che, [59][60][61] among others, Pt acetylides have ar ich photochemistry.A bsorption bands at l < 400 nm are intraligand p!p* transitions, and bands at lower energies correspond to 1 [dp(Pt)!p*(tpy)] metal-to-ligand charget ransfers ( 1 MLCT) and ac ombination of overlapping 1 MLCT and 1 [p(CCR)!p*(tpy)] ligand-to-ligand ( 1 LLCT) transitions. In the solid state or in dinuclear complexes, short PtÀPt distances (< 3.5 , [40] and as short as 2.8 [62] )d estabilize the filled d z 2 orbitals, resulting in lower energy 1 [ds*!p*(tpy)] metal-metal-to-ligand charge transfer transitions ( 1 MMLCT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation